Code Comments for Quantum Software Development Kits: An Empirical Study on Qiskit - zenghui zhou (22207153) (2025)
Dataset and code for “Code Comments for Quantum Software Development Kits: An Empirical Study on Qiskit” This repository provides: Data: The CC4Q dataset containing Code–Comment Pairs (CCPs) and Sentence-level Code Comment Units (SCCUs) extracted from popular quantum software libraries (e.g., Qiskit). Final labeled data are stored in `data/final_data/`. Annotations and labels: Open coding results and manually annotated labels are available in `label/`. Model-inferred labels are saved in `model/`. Code: Scripts for data extraction, comment segmentation, and baseline classification models. A more detailed description can be found in README.md